Delta-like Ligand 4 Identifies a Previously Uncharacterized Population of Inflammatory Dendritic Cells That Plays Important Roles in Eliciting Allogeneic T-cell Responses in Mice - Mochizuki, Kazuhiro (2013)
Graft-versus-host disease (GVHD) reflects an exaggerated inflammatory allogeneic T-cell response in hosts receiving allogeneic hematopoietic stem cell transplantation (HSCT). Inhibition of pan-Notch receptor signaling in donor T cells causes reduction of GVHD. However, which Notch ligand(s) in what antigen-presenting cells are important for priming GVH reaction remains unknown. We demonstrate that δ-like ligand-4 (Dll4) and Dll4-positive (Dll4(hi)) inflammatory dendritic cells (i-DCs) play important roles in eliciting allogeneic T-cell responses. Host-type Dll4(hi) i-DCs occurred in the spleen and intestine of HSCT mice during GVHD induction phase. These Dll4(hi) i-DCs were CD11c(+)B220(+)PDCA-1(+), resembling plasmacytoid DCs (pDCs) of naïve mice. However, as compared to unstimulated pDCs, Dll4(hi) i-DCs expressed higher levels of costimulatory molecules, Notch ligands Jagged1 and Jagged2 and CD11b and, produced more Ifnb and Il23 but less Il12. In contrast, Dll4-negative (Dll4(lo)) i-DCs were CD11c(+)B220(−)PDCA-1(−), and had low levels of Jagged1. In vitro assays showed that Dll4(hi) i-DCs induced significantly more IFN-γ- and IL-17-producing effector T cells (3- and 10-fold, respectively) than Dll4(lo) i-DCs. This effect could be blocked by anti-Dll4 antibody. In vivo administration of Dll4 antibody reduced donor alloreactive effector T cells producing IFN-γ and IL-17 in GVHD target organs, leading to reduction of GVHD and improved survival of mice after allogeneic HSCT. Our findings indicate that Dll4(hi) i-DCs represent a previously uncharacterized i-DC population distinctive from steady state DCs and Dll4(lo) i-DCs. Furthermore, Dll4 and Dll4(hi) i-DCs may be beneficial targets for modulating allogeneic T-cell responses, and could facilitate the discovery of human counterparts of mouse Dll4(hi) i-DCs.